Clinical and pathophysiological study of patients with vertigo at SAIMS, Indore - Patni, Digant; Tyagi, Alok; Munjal, Vishal R. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: This was a prospective, descriptive study performed by collecting and analyzing the results of vestibular exams, evoked myogenic potential tests, pure tone audiometry test and impedence test performed in the Otorhinolaryngology Department of Sri Aurobindo Institute of Medical Sciences, Indore. Methods: This was a prospective, descriptive study performed by collecting and analyzing the results of vestibular exams, evoked myogenic potential tests, pure tone audiometry test and impedence test performed in the Otorhinolaryngology Department of Sri Aurobindo Institute of Medical Sciences, Indore. Results: In age group of 20 to 60, maximum number of patients were in group of 31-40 (16), followed by 51-60 (15), followed by 20-30 (24.) Maximum positive seen in Romberg (07), followed by nystagmus (06), followed by Dix-Hallpike (06). The patients in our study (30 out of 50) were suffering from hypertension. Two patients were of Meniere’s disease and rest 16 were of SNHL, 08 were of SNHL and BPPV combined. The rest of the cases were of mixed hearing loss and other central hearing loss causes will have be ruled out. Conclusions: The main aim of study is to study clinicopathological aspects in patients with vertigo. We also studied incidence of SNHL in our study. It has been established by this study that hypertension is one the major causes of vertigo in patients whereas VEMP has not proven to be very beneficial in our study to see peripheral vertigo patients. Most of the patients with BPPV also had a normal cVEMP which showed that it was not a very reliable instrument in BPPV.